DESIGN OF A PROTOTYPE HYDRO COIL TURBINE APPLIED AS MICRO HYDRO SOLUTION - Arik Aprilliyanto; Indarto -; Prajitno - (Master in Systems Engineering, 2013)
This study deals with the effort to release new revolution of renewable energy concept. Key issue in generating hydro power from low head, low flow sources until now has been impractical, expensive in efficient and complex technology. The idea of using Hydro Coil instead of turbine gives an economic advantage that it is relatively cheaper. The apparatus allows us to exploit sides that would not be practical at all for conventional small hydroelectric power.Hydro Coil turbine in experimental prototype has been designed, built and tested. The turbine includes 4 inches acrylic with ribbon-like curved shape insert, which present a gradual curve of approximately 70 degrees from the axial flow of water progressing to a tightly curved angle perpendicular to the flow of water at the exit point. The gradual curve is used to reducing the axial velocity of water, thereby further as consequence of transfer energy from water to ribbon, thus the central axle and ribbon rotated. This rotation is initiated at the low frequency coil, with energy incrementally transferred as water, hitting the low frequency coil, turning the ribbon slowly, progressing gradually to higher frequency, tight coil where maximal energy to the transfer occurs.Characteristics and efficiency of Hydro Coil turbine can be identified after laboratory experimental already finished. Turbine efficiency in 92.93% of this prototype exceeds expectation in the experiments. It thus demonstrates the promising potential of Hydro Coil technology to extract power from incoming water flow in low head sources.